O roli nauczyciela w edukacji międzykulturowej (Szkoła - Zawód - Praca, 2020)
In a globalizing world, interaction with different cultures has become a matter of everyday life. Multiculturalism is determined by the awareness of cultural differences and, at the same time, by opening or closing oneself to the otherness, and entering into interactions. The article discusses the role of the teacher in multicultural and intercultural education. Moreover, the author discusses multicultural and intercultural competences as well as teacher’s role related to their development. The teaching and educational work contributing to translating the theoretical knowledge, and postulates of multicultural education, into practical situations which take place at school are also defined in the article.